2022
DOI: 10.1002/nop2.1274
|View full text |Cite
|
Sign up to set email alerts
|

Development and applicability of a dignity‐centred palliative care programme for people with idiopathic pulmonary fibrosis: A qualitative‐driven mixed methods study

Abstract: Idiopathic pulmonary fibrosis (IPF) is a rare, intractable and fatal disease (Mei et al., 2022). Maher et al. (2021) target literature review covering 2009 to 2020 found 22 studies covering 12 countries. The adjusted incidence was from .09-1.30 per 10,000. The adjusted prevalence was from 3-4.51 per 10,000. The lowest incidence and prevalence were found in the Asia-Pacific countries with the exception of South Korea with the highest of all countries. Globally, the incidence is increasing (Maher et al., 2021;St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…13 studies reported narrative results ( supplement 2.2 ). The importance of HCPs and peer support was highlighted most often [ 25 , 28 , 30 , 39 , 48 , 52 , 67 , 92 , 99 ]. Support from HCPs was sought in various settings ( i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 studies reported narrative results ( supplement 2.2 ). The importance of HCPs and peer support was highlighted most often [ 25 , 28 , 30 , 39 , 48 , 52 , 67 , 92 , 99 ]. Support from HCPs was sought in various settings ( i.e.…”
Section: Resultsmentioning
confidence: 99%
“…62 (71%) studies reported no AEs. 12 (14%) studies reported deaths in the intervention group [ 29 , 35 , 43 , 45 , 49 , 52 , 54 , 66 , 74 , 79 , 86 , 99 ] and 14 (16%) reported other reasons for not completing the intervention [ 27 , 34 , 38 , 42 , 46 , 50 , 52 , 55 , 60 , 72 , 73 , 81 , 100 , 108 ]; however, no links between the study intervention and death or noncompletion were reported. Reasons for noncompletion included acute exacerbation, other respiratory-related issues, nonrespiratory health issues and personal reasons such as lack of motivation, being called to receive lung transplantation and transportation problems.…”
Section: Resultsmentioning
confidence: 99%